The Goursat problem for one hyperbolic system of the third order differential equations with two independent variables - Aleksander A Andreev; Julia O Yakovleva (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2011)
The solution of the Goursat problem for the system of the diﬀerential equations of the third order is received on the basis of Riemann method. The Riemann matrix expressed in terms of hypergeometric functions with matrix argument is received, using it the solution of Goursat problem for the system of the linear hyperbolic equations of the third order is constructed.